Perception affection of parents and self-compassion on late adolescence in Yogyakarta - Rahayu, Ni Luh Putu Diah Putri; Purnamasari, Santi Esterlita (Universitas Mercu Buana Yogyakarta, 2022)
Self-compassion is important for late adolescence because it will have a positive impact, especially when experiencing a problem, but affectionate self-compassion is also influenced by adolescents' perceptions of the love given by their parents. Based on this, this study aims to determine the relationship between perceptions of parental love and self-compassion, where this study was applied to the subject of late adolescence as many as 102 people living in Yogyakarta with the age of 18-21 years. Data collection in this study used a scale, namely the Perception Scale of Parental Love and the Self-Compassion Scale, where the data analysis technique used was the Product Moment Technique correlation of Karl Pearson. When adolescents have a positive perception of their parents' affection, late adolescence will have high self-compassion. These findings indicate that there is a significant positive relationship between perceptions of parental affection and self-compassion.